Dynamic CT angiography for therapy evaluation after transarterial chemoembolization of hepatocellular carcinoma - Saake, Marc; Seuß, Hannes; Hammon, Matthias; Ellmann, Stephan; May, Matthias; Uder, Michael; Schmid, Axel (Acta Radiologica, 2019)
Background: Liver dynamic computed tomography (CT) is an established method for pre- and post-interventional evaluation of hepatocellular carcinoma. To date only the liver parenchyma and perfusion information of dynamic CT has been evaluated widely. Purpose: To evaluate the vascular information contained in dynamic CT datasets. Material and Methods: Dynamic CT performed one day after transarterial chemoembolization (60 mL of contrast medium, 6 mL/s, 40 s scan duration) were retrospectively evaluated. Conventional slice and angiographic maximum-intensity-projection reconstructions were calculated on a multi-modality post-processing platform. Datasets were evaluated for viable tumor, anatomy of the vasculature, and potential tumor-feeding vessels. The results were compared to digital subtraction angiography images. Results: In total, 94 treated hepatocellular carcinoma nodules were evaluated (62 dynamic CT scans, 46 patients [34 men; mean age = 69 years]). Forty-six partially viable tumors were diagnosed after transarterial chemoembolization. In all of these, tumor-feeding vessels were found in dynamic CT. Seventeen suspected extra-hepatic tumor feeders were reported, of which 14 had not been found during previous transarterial chemoembolization. Conclusion: Dynamic CT is useful in post-interventional imaging of hepatocellular carcinoma after transarterial chemoembolization due to its ability to detect residual viable tumor parts and to show previously unknown intra- and extra-hepatic tumor-feeding vessels.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Abdomen; chemoembolization; computed tomography angiography; interventional; liver